Investigation of some probiotic and technological properties of lactic acid bacteria strains isolated from artisanal sheep milk cheese and their growth in goat milk - Ruiz, María Julia (2024)
The objective of this study was to assess the probiotic and technological properties of lactic acid bacteria (LAB) isolated from artisanal sheep milk cheeses for potential use in dairy products made from goat milk. Strains studied were Lacticaseibacillus paracasei LC6, Lactiplantibacillus plantarum LP48, Lactococcus lactis subsp. hordniae LH69 andLeuconostoc mesenteroides LM99. The criteria studied were fermentative capacity, carbohydrate fermentation profile, β-galactosidase (lactase) activity, auto-aggregation capacity, hydrophobicity, antimicrobial activity, resistance to simulated gastric secretion, bile resistance, and resistance to different pH and salts concentrations, as well as growth and viability in goat milk. In general, the strains studied showed characteristics compatible with potential probiotic effects. However, according to criteria studied, L. plantarum LP498 best met the conditions; it was compatible with probiotic potential under all the conditions considered and showed noteworthy differences compared to the other micro-organisms studied, particularly in its capacity for self-aggregation and pH resistance. Therefore, L. plantarum LP48 could be adequate for the manufacture of artisanal goat milk products.